2007
DOI: 10.1002/prot.21697
|View full text |Cite
|
Sign up to set email alerts
|

Structural rationalization of novel drug metabolizing mutants of cytochrome P450 BM3

Abstract: Three newly discovered drug metabolizing mutants of cytochrome P450 BM3 (van Vugt-Lussenburg et al., Identification of critical residues in novel drug metabolizing mutants of Cytochrome P450 BM3 using random mutagenesis, J Med Chem 2007;50:455-461) have been studied at an atomistic level to provide structural explanations for a number of their characteristics. In this study, computational methods are combined with experimental techniques. Molecular dynamics simulations, resonance Raman and UV-VIS spectroscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 60 publications
2
40
0
Order By: Relevance
“…2), which is in agreement with the observation that a high proportion of drugs are weak bases (Manallack, 2008). Three of the six BM3 mutants (M01, M02, and M11) that were chosen for the drug library screening have previously been demonstrated to display different metabolic activities (van Vugt- Lussenburg et al, 2007;Stjernschantz et al, 2008). The other three mutants (MT35, MT38, and MT43) were selected because they contained mutations at different residues in the active site, which was expected to result in changes in metabolic activity and diversity (Carmichael and Wong, 2001;Li et al, 2001b;Dietrich et al, 2009).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…2), which is in agreement with the observation that a high proportion of drugs are weak bases (Manallack, 2008). Three of the six BM3 mutants (M01, M02, and M11) that were chosen for the drug library screening have previously been demonstrated to display different metabolic activities (van Vugt- Lussenburg et al, 2007;Stjernschantz et al, 2008). The other three mutants (MT35, MT38, and MT43) were selected because they contained mutations at different residues in the active site, which was expected to result in changes in metabolic activity and diversity (Carmichael and Wong, 2001;Li et al, 2001b;Dietrich et al, 2009).…”
Section: Resultssupporting
confidence: 86%
“…The four P450 BM3 mutants, M01, M02, M05, and M11 (see Supplemental Table S1), have previously been demonstrated to display good expression and activity toward drug-like compounds (van Vugt- Lussenburg et al, 2007;Damsten et al, 2008a,b;Stjernschantz et al, 2008) and were therefore included in the mutant library. Ten novel mutants (see Supplemental Table 1) using both M01 and M11 as template were additionally selected from an already existing library (J. S. van Leeuwen and E. Stjernschantz, unpublished results).…”
Section: Resultsmentioning
confidence: 99%
“…In recent studies, several lines of evidence supporting our proposal have been reported. CYP102A1 mutants were found to generate human drug metabolites by oxidizing various drugs, including clozapine (Damsten et al, 2008), diclofenac (Damsten et al, 2008), acetaminophen (Damsten et al, 2008), 3,4-methylenedioxymethylamphetamine (Stjernschantz et al, 2008), dextromethorphan (Stjernschantz et al, 2008), phenacetin , verapamil (Sawayama et al, 2009), and astemizole (Sawayama et al, 2009). CYP102A1 mutants can also oxidize several human P450 substrates, including 7-ethoxycoumarin (Kim et al, 2008b), coumarin (Park et al, 2010), chlorzoxazone (Park et al, 2010), and resveratrol (Kim et al, 2009), to generate human metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the directed evolution, the use of rational design for predicting protein structure and calculating the precise molecular interactions between the substrate and active site of the enzyme can be successfully applied to the engineering of CYP102A1 to a specific medium chain p-nitrophenoxycarboxylic acid (Li et al, 2001). More recently, computational methods combined with experimental techniques including molecular dynamics simulations, resonance Raman, and UV-VIS spectroscopy, as well as coupling efficiency and substrate-binding experiments, could be successfully applied to the engineering of CYP102A1 to metabolize human CYP2D6 substrates, 3,4-methylenedioxymethylamphetamine and dextromethorphan (Stjernschantz et al, 2008).…”
Section: Kim Et Almentioning
confidence: 99%
“…Several mutants of Bacillus megaterium P450 BM3 (CYP102A1) generated through rational design or directed evolution could oxidize several human P450 substrates to produce authentic metabolites with higher activities (Otey et al, 2005;Yun et al, 2007 and references therein;Kim et al, 2008a;Stjernschantz et al, 2008). These recent ABBREVIATIONS: P450, cytochrome P450; HPLC, high-performance liquid chromatography; TTNs, total turnover numbers; GC-MS, gas chromatograph-mass spectrometry.…”
mentioning
confidence: 99%